IMPROVING STUDENTSâ€™ SPEAKING SKILL THROUGH STORY TELLING TECHNIQUE TO THE ELEVENTH GRADE STUDENTS OF SMA SWASTA KATOLIK BUDI MURNI 2 MEDAN - Tambunan, Veronika Dasniati; Lumban Raja, Viator; Sari, Anna Stasya Prima (Kairos English Language Teaching Journal, 2020)
This research was conducted in order to improve studentsâ€™ speaking skill through story telling technique to the eleventh grade students of SMA Swasta Katolik Budi Murni 2 Medan. In conducting this research, the writer used Classroom Action Research (CAR). This reaearch showed that teaching speaking skill through story telling technique to the eleventh grade students of SMA Swasta Katolik Budi Murni 2 Medan could improve their speaking skill. The result of the this research showed that the studentsâ€™ responses after being taught by using story telling technique are very good. The result of the test showed the studentsâ€™ mean score in pretest is 57,37 with 20% of the students got score â‰¥ 70, in formative test mean score is 70,85 with 60% of t he students got score â‰¥ 70Â and in posttest mean score is 80,05 with 88,57% of the students got score â‰¥ 70. The research findings showed tha the application of story telling technique could improve the students speaking skill. It is advisable that English teachers apply story telling technique as a technique in order to improve their studentsâ€™ speaking skill. Â